Transborder Higher Education Students: Living in Mexico and Studying in the U.S. - ROCHA ROMERO, David; ORRACA ROMANO, Pedro Paulo (Frontera Norte, 2018)
There is a small number of transborder students who reside in Mexico but go to school in the United States. Less than 2.5 percent of students residing in border cities such as Tijuana, Ciudad Juarez or Nogales, are transborder students. Pupils born in Mexico that go to school in the United States represent less than 1 percent of the student population in all educational levels. Country of birth, having parents that are international commuters, and household income are elements that enable or limit transborder membership. High earnings are the central factor for Mexicans that want to go to school del otro lado.